Modeling the catalytic conversion of anthracene oil fraction to light aromatics over mesoporous HZSM-5. (1st July 2022) - Wang, Linyang; Yao, Qiuxiang; Liu, Yongqi; Ma, Duo; He, Lei; Hao, Qingqing; Chen, Huiyong; Sun, Ming; Ma, Xiaoxun
Graphical abstract: Highlights: Simulation anthracene oil was used to evaluate the conversion of catalysts to BTXN. Mesoporous HZSM-5 were synthesized by different amount of mesoporous agent. Experimental yield of BTEXN is higher than theoretical during mixed MCs pyrolysis. Hydrogen species derived from C22 pyrolysis promote the hydrogenation of PAHs. Both suitable acidity and pore size are conducive to improve the yield of BTEXN. Abstract: Silanization of zeolite units has been proved to be an effective way to improve the hierarchical porosity of HZSM-5. Mesoporous HZSM-5 (YJGW-X: X = 0, 5, 10) were synthesized by adopting phenyl amino propyl trimethoxy silane (YJGW) with different addition (0 wt%, 5 wt% and 10 wt%), followed were applied to investigating the interaction between the compounds of various categories during the conversion process of anthracene oil fraction of low temperature coal tar. Model compounds (MCs), which including naphthol (Nap-ol), methyl naphthalene (Nap-met), methyl anthracene (Ant-met) and C22 alkanes (C22), are selected as raw materials to investigate the conversion progress of anthracene oil fraction of low temperature coal tar using Py-GC/MS. Results show that YJGW addition has a significant role on the acidity and pore size. Besides, the higher aromatic selectivity exhibited by YJGW-5 and YJGW-10 compared to YJGW-0 in the catalytic pyrolysis of single MCs indicates that the addition of YJGW does facilitate the hydrocracking of polycyclic aromatics hydrocarbons to prepare small reactive molecules. When mixed MCs pyrolyzed using YJGW-X, the experimental yield of BTEXN (benzene, toluene, ethyl-benzene, xylene and naphthalene) is higher than theoretical one. When pyrolyzed at 450 °C, the highest experimental yield (2578.35 mg/kg) of BTEXN is obtained using YJGW-10, owing to its appropriate pore structure and acidity. Moreover, the possible formation mechanism of BTEXN derived from MCs catalytic pyrolysis was proposed on the basis of structural features and catalytic performances of YJGW-X.